2020
DOI: 10.1007/s00432-020-03202-0
|View full text |Cite
|
Sign up to set email alerts
|

Selected protein expression in a new prognostic model for patients with non-muscle-invasive bladder cancer

Abstract: Introduction After transurethral resection of a bladder tumor, patients frequently have a recurrence of the disease, thereby requiring adjuvant therapy. Purpose The study aimed to determine the prognostic value of expression levels of p53, Ki-67, and survivin, and to develop a new prognostic model for patients with non-muscle-invasive bladder cancer (NMIBC) after transurethral resection of a bladder tumor. Methods The study group consisted of 101 patients with primary NMIBC. Univariate followed by multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…However, in NMIBC patients, many recurrences are not related to primary UC that was surgically removed, such as by incomplete TURB. For the reasons mentioned here, unlike previous studies reporting that Ki67 is related to prognosis under certain conditions, in NMIBC ( 43 , 44 ), we found no significant relationship between Ki67 expression levels and recurrence/progression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in NMIBC patients, many recurrences are not related to primary UC that was surgically removed, such as by incomplete TURB. For the reasons mentioned here, unlike previous studies reporting that Ki67 is related to prognosis under certain conditions, in NMIBC ( 43 , 44 ), we found no significant relationship between Ki67 expression levels and recurrence/progression.…”
Section: Discussioncontrasting
confidence: 99%
“…Ki67 is a DNA-bound protein activated only during the proliferation phase and is not detected during cell cycle quiescence. Studies on Ki67 in UC have reported it as a prognostic factor for recurrence and progression in upper tract UC ( 19 , 42 ) NMIBC after TURB ( 43 , 44 ). In the present study, we found a correlation between higher stages of UC and increased Ki67 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it would be more accessible in health-providing centers. Some studies had successfully validated protein prognostic model in malignancies, such as bladder cancer, lung adenocarcinoma and diffuse large B-cell lymphoma [22][23][24]. The protein models demonstrated vital role for predicting prognosis, which including bladder cancer, esophageal squamous cell carcinoma and pancreatic ductal adenocarcinoma [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…After screening, a full‐text review was performed for 201 articles. According to the inclusion criteria, we finally identified 72 studies comprising 28 139 patients eligible for the meta‐analysis [12–83]. The demographics of each included study are shown in Table 1 and Table S2.…”
Section: Resultsmentioning
confidence: 99%